2011
DOI: 10.5812/asjsm.34755
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Patterns of Subjective Experiences and Self-Regulation during Ramadan Fasting among Elite Archers: A Qualitative Analysis

Abstract: Purpose: Some major competitions (e.g. London Olympics, 2012) are scheduled during the Ramadan fasting month. Little attention has been given to explore the archers' performance related subjective experiences with a qualitative method. Therefore, this study addressed individual archers' subjective experiences within the framework of self-regulation during Ramadan. Methods:Eleven elite Malaysian Muslim fasting archers volunteered to participate in the study. Grounded theory was the qualitative approach used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In their choice of repetitions, the athletes declared favoring the quality of their training rather than quantity with a reduction in the number of sessions per week (34% for a reduction in the number of sessions). This choice of strategy has been recommended to athletes in order to avoid possible metabolic stress, which could be caused by daytime fasting, as well as by chronic sleep deprivation resulting from the cumulative loss over several days (13,16,26,27).…”
Section: Training and Recoverymentioning
confidence: 99%
See 2 more Smart Citations
“…In their choice of repetitions, the athletes declared favoring the quality of their training rather than quantity with a reduction in the number of sessions per week (34% for a reduction in the number of sessions). This choice of strategy has been recommended to athletes in order to avoid possible metabolic stress, which could be caused by daytime fasting, as well as by chronic sleep deprivation resulting from the cumulative loss over several days (13,16,26,27).…”
Section: Training and Recoverymentioning
confidence: 99%
“…Such a disturbance in sleep patterns, which could be the cause of a disturbance in eating habits and fluid intake, has a direct effect on human circadian rhythms (28)(29)(30). This can give general feelings of discomfort and fatigue, which could have a negative influence on physical performance (13,26). Several studies have shown that an average of 8 hours of nighttime sleep, even with a cumulative decrease over the Ramadan period, Ramadan fasting does not compromise the quality of sleep (3,31).…”
Section: Training and Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…Research related to Ramadan and performance in Malaysia have been helpful in understanding how Ramadan fasting affects sports performance (see Aziz & Weileen, 2008;Roy et al, 2011a;Roy et al, 2011b;Singh et al, 2011). Despite the existence of such research, there is a deficit of literature that examines the distinction and essential socio-cultural influences in sport setting during Ramadan.…”
Section: Introductionmentioning
confidence: 99%
“…Schinke et al (2010) proposed adaptation as a comprehensive intervention strategy for elite athletes where he emphasized the importance of providing additional psychological guidance and practical knowledge on how to transfer the learning from a sterile environment to a real world context. Roy et al (2011a) studied the temporal patterns of subjective experiences and self-regulation during Ramadan fasting among Malaysian elite archers. This study reported an increase in experiences related to mental factors in the latter phase of Ramadan fasting.…”
Section: Social Panopticon and Adaptationsmentioning
confidence: 99%